Cochlear implantation in Ménière's disease: a systematic review of literature and pooled analysis. (2nd June 2020) - Di Berardino, Federica; Conte, Giorgio; Turati, Federica; Ferraroni, Monica; Zanetti, Diego
Abstract: Objective: The aim of this study was to evaluate the effect of cochlear implantation (CI) in advanced Ménière's disease (MD). Design: The initial search on PubMed, EMBASE, and Cochrane databases yielded 171 articles; no language restriction was applied. Study sample: A total of 11 articles met the inclusion criteria and were included in this systematic review. Six articles provided patient-level data on improvement in speech recognition testing after CI. Results: The methodological quality of included studies was assessed by examining the study design, level of evidence, method of measurement and adequacy of outcome reporting. A random-effect model was fitted for calculating weighted means. Post-operative improvement in word recognition score (WCS) was 50.8% (95% confidence interval: 34.6–67.1%); general improvement of vestibular symptoms after CI was found in 67% of the pooled patients; when reported in the studies, quality of life (QoL) and tinnitus were also generally improved after CI. Conclusions: CI in advanced MD is a valid option providing good outcomes in terms of speech performances, regardless of the disease duration, uni- or bilaterality, age at implantation, previous therapeutic procedures and stage of activity of MD.